A Life of Crime : My Career in Forensic Science - Lucas, Douglas; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
A Life of Crime: My Career in Forensic Science chronicles the career and experiences of world-renowned forensic scientist, Dr. Douglas Lucas. It is the culmination of his decades-worth of work in the field, developing innovative techniques that have revolutionized several aspects of forensic science. It is part professional reference, part career guide, part instructive reference for students wishing to entering the to enter the field, and wholly autobiographical. Dr. Lucas chronicles a number of the high-profile cases he s worked on firsthand. This includes both the logistical problem-solving of case management how to process and handle the evidence in addition to the testing, analysis and processes he went through, and developed, along the way. Such cases include mass disaster plane crashes, arson, IEDs and explosives, poisonings, missing persons, and homicides, to name just a few. Dr. Lucas has encountered and seen just about everything a forensic professional can see. In addition to the in-depth discussion, development, and philosophy of forensic science as a discipline, the book also discusses the balance of personal and professional life. This is a vital, but little thought of aspect that becomes a conspicuous reality of working in the field: namely, delving into the science, and dealing with those personal emotions, work conflicts, and ethical conundrums that a professional regularly encounters. Forensic professionals, investigators, and students regardless of background or discipline will find this a fascinating look "behind the curtain" at one of the most decorated, innovative, and respected members of the field over the last 50 years.
Prologue: Flight 621 -- 1. The Early Years -- 2. The Fledgling Forensic Scientist -- 3. "Point Zero Eight": Forensic Science Influences the Law -- 4. The Courtroom: "What on Earth Am I Doing Here?" -- 5. Broadening Horizons: There Is More to This Than Just Alcohol! -- 6. Screech and Seal Flipper Pie: Fire and Politics in Newfoundland -- 7. Carbon Monoxide: "Death and the Dark-Haired Maiden" -- 8. Nitroglycerine and Explosions: Some Things Cant Be Learned in the Laboratory -- 9. An Explosion in A Dynamite Plant: "Holy ShitThis Stuff Is Dangerous" -- 10. Dealing With IEDs: "There Has To Be A Better Way" -- 11. Canadas Guy Fawkes -- 12. Mr. Miscellaneous: "Can You Do Something With This?" -- 13. Missing Person or Homicide? Regina v. Arthur Kendall -- 14. How to Get a New Lab? Regina v. Wayne Ford -- 15. The Attorney Generals Lab Gets a New Name, and a New Director -- 16. "Get Involved" They Told Me, So I Did: Professional Associations -- 17. Last Word Society Stories, #1 (1979): "Was Tom Thomson Murdered?" or "Whose Bones Are Buried Under That Spruce Tree?" -- 18. Last Word Society Stories # 2 (1983): The Assassination of Thomas DArcy McGee, "Look for the Tailor with the Red Whiskers." -- 19. Last Word Society Stories # 3 (1988): Arsenic and Old Ice, The Death of Charles Francis Hall -- 20. Miracle in Mississauga: "Lets Get the Hell Out of Here" -- 21. The Baby Deaths at Sick Kids Hospital: "George the Moose Was Still Standing" -- 22. Introduction of DNA Profiling: "If You Are Going to Do It, Do It Right!" -- 23. The Guy Paul Morin Case: "A Tragedy of Errors" -- 24. The Steven Truscott Case: Wrongful Conviction or Factual Innocence? -- 25. Retirement, Part 1: "So, What Do I Do Now?" -- 26. Retirement, Part 2: My Final Presentation -- Appendix A. Curriculum Vitae
Includes bibliographical references and index.
Also available in print format.
Keywords: Forensic scientists -- Canada -- Biography; Forensic sciences -- Canada; Criminal investigation -- Canada; Criminal investigation; Forensic sciences; Forensic scientists; LAW / Criminal Law / General; Electronic books